Preparation Of In-Situ Carbides Reinforced Hybrid Copper-Based Composite By Mechanical Alloying And Its Characterization - Le , Minh Hai (2010)

(untitled)
The goal of this research work is to investigate the feasibility of the synthesis of two distinct in-situ carbides (NbC and TiC) simultaneously in a copper matrix via mechanical alloying and powder metallurgy from elemental powders of Cu, Nb, Ti and graphite. Three mixtures of starting powders with compositions corresponding to Cu-10vol.%NbC-10vol.%TiC, Cu-15vol.%NbC-15vol.%TiC and Cu-20vol.%NbC- 20vol.%TiC were mechanical alloyed using a planetary ball mill for 5, 10, 20 and 30 hours. The as-milled powders then were cold pressed at compaction pressure in range of 500-1000 MPa and sintered in a vacuum sintering furnace for 1 hour at different temperatures from 700 to 1000oC